Productive characterization and nutritive value of pastures implanted on the 7 Quintas Farm, Waco-Kungo, Angola (Revista de Ciências Agroveterinárias, 2024)
The present study was developed with the objective of characterizing the productive potential and nutritional value of forage species implemented on the farm, from October 2018 to March 2019. The species identified are Brachiaria Brizantha and the genus Cynodon.The experimental method used was the direct technique (square method) which consists of six metal cages measuring 0.50 m x 0.50 m fixed, three for each plot. Every 30 days, the forage mass was cut in each of the cages at a height of 10 cm from the ground andsent to the Central Agroindustrial laboratory of the Ministry of Agriculture in Luanda for bromatological analysis. Variables analyzed: mineral matter (MM) 10.7% and 7.6%; humidity (U) 24.12% and 32.9%; crude protein (CP) 3.93% and 3.19%; crude fiber (FB) 0.35% and 3.19%; ether extract (EE) 1.14% and 0.98%; calcium (Ca) 0.39% and 0.33%, phosphorus (P) 0.12% and 0.16%; potassium (K) 3.56% and 2.47% of averages respectively for the identified species are Brachiaria Brizantha and genus Cynodon.The non-nitrogen extract, carbohydrates, gross energy, pasture productivity and stocking capacity were calculated. DM productivity was considered relatively low in both genera with an average of 195.06 kg and 178.08 kg for Brachiaria Brizantha and genus Cynodon,respectively. However, the data obtained can serve as a basis for continuing studies, in addition to its importance for establishing a database on the productivity and nutritional value of pastures, given the lack of this information in Angola.
Keywords: produtcive characterization; pastures; Nutritional value